EDUKASI GIZI DAN PENERAPAN ROTI FUNGSIONAL DADIAH PADA IBU HAMIL UNTUK PENCEGAHAN STUNTING DI KABUPATEN LIMAPULUH KOTA - Helmizar Helmizar; Ferdinal Ferry; Faza Yasira Rusdi; Utami Ariyasra; Sri Rahma Sari; Restu Sakinah (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Stunting is the cronic malnutrition that was considered to still be a severe problem in Indonesia because the prevalence rate is still above 20%. Stunting prevention can be done by providing nutrition, health services, and using local food, such as dadih, for pregnant women. This service aims to increase capasity of mothers' knowledge about pregnancy through nutritional education and the application of processed dadih products in the form of functional dadih bread to pregnant women to prevent stunting in The Limapuluh Kota districts. The lecture method was used in n this activity provide free supplemental food to pregnant women in Lima Puluh Kota Regency. carried out on July 31 2023, by providing nutritional education and the application of dadiah functional bread to pregnant women. Other activities included in this service are ultrasound examinations and nutritional status for pregnant women. Acceptance of pregnant women's consultation every day for 1 month. The weight of pregnant women was measured before and after giving curd functional bread. The results of this activity showed that the acceptability of functional curd bread was good proven by the remaining products provided, only 25% of all products consisting of bread and curd vla. The conclusion of this community service is an effect of giving functional curd bread on weight gain of pregnant women.